VALUES OF JOGJA EDUCATION THROUGH ART LEARNING AT ECCE INSTITUTIONS - Joko Pamungkas; Harun Harun; Septika Cahya Rahmawati; AD Dieni Maulana Rizka (Pelopor Publikasi Akademika, 2023)
This study aims to know and identify Jogja values through art learning in kindergartens of the Special Region of Yogyakarta. This research method is with a qualitative approach with the process of data collection through observation, interviews and documentation as well as triangulating data to obtain data devalidation. The results of this study found that this art learning includes the development of children's dance, songs and children's traditional dolanan. The values contained in Jogja are the main ingredients in pouring this art learning material. These values are Hamemayu Hayuning Buwana, Sangkan paraning dumadi and manunggaling kawula gusti. In teaching these values, techniques in art learning that cannot be separated are elements of appreciation, exploration and expression